Contrasting opioid use for pain management in microvascular head and neck reconstruction: an international study. Issue 11 (November 2022) - Weyh, A.M.; Pucci, R.; Busby, E.; Kansal, L.; Joy, R.; Bunnell, A.; Valentini, V.; Dyalram, D.; Pattatheyill, A.; Figari, M.; Boccalatte, L.; Larrañaga, J.; et al.
Abstract: Opioids are often the mainstay of postoperative pain management, despite strong evidence of their ill effects and potential for long-term addiction. The goal of this study was to quantify opioid use and contrast pain management strategies of multiple international institutions performing fibula free flap reconstruction. A retrospective multicenter cohort study was designed, including five international centers. For inclusion, the patients had to have undergone a primary fibula free flap reconstruction of the mandible. A total of 185 patients were included. The median opioid use across all centers at 72 hours was 133 oral morphine equivalents. The highest utilization was in the USA ( P  < 0.001), which was approximately six times that of Italy, four times that of Argentina, and twice that of India, despite all centers performing a similar procedure. Based on this study there are clear differences in prescribing practices and ideologies among surgeons from different countries.